Yos9p and Hrd1p mediate ER retention of misfolded proteins for ER-associated degradation - Izawa, Toshiaki (The American Society for Cell Biology, 2012)
The endoplasmic reticulum (ER) has an elaborate quality control system, which retains misfolded proteins and targets them to ER-associated protein degradation (ERAD). To analyze sorting between ER retention and ER exit to the secretory pathway, we constructed fusion proteins containing both folded carboxypeptidase Y (CPY) and misfolded mutant CPY (CPY*) units. Although the luminal Hsp70 chaperone BiP interacts with the fusion proteins containing CPY* with similar efficiency, a lectin-like ERAD factor Yos9p binds to them with different efficiency. Correlation between efficiency of Yos9p interactions and ERAD of these fusion proteins indicates that Yos9p but not BiP functions in the retention of misfolded proteins for ERAD. Yos9p targets a CPY*-containing ERAD substrate to Hrd1p E3 ligase, thereby causing ER retention of the misfolded protein. This ER retention is independent of the glycan degradation signal on the misfolded protein and operates even when proteasomal degradation is inhibited. These results collectively indicate that Yos9p and Hrd1p mediate ER retention of misfolded proteins in the early stage of ERAD, which constitutes a process separable from the later degradation step.